Seismicity in a Transpressional Volcanic Arc: The Liquiñe‐Ofqui Fault System in the Puyuhuapi Area, Southern Andes, Chile (44°S). Issue 11 (24th November 2020) - Pérez‐Estay, Nicolás; Yáñez, Gonzalo; Crempien, Jorge; Roquer, Tomás; Cembrano, José; Valdenegro, Pablo; Aravena, Diego; Arancibia, Gloria; Morata, Diego
Abstract: Understanding the relationship between crustal faults and volcanic activity in transpressional environments is a main goal in geosciences and could help to understand geothermal resources and evaluate geological hazards. In the Andean Southern Volcanic Zone (SVZ), Chile, recorded seismicity is scarce, and few studies have evaluated the relationship between volcanic activity and crustal faults from seismic observations. Thus, in this study, we deployed a seismic network for almost 1 year to understand the brittle deformation of the upper crust within the Puyuhuapi area, located at 44°S in the SVZ. We analyzed the location and kinematics of seismicity together with previously published field structural geological data. Considering these results, we developed an integrative tectonic model for the area and discussed which faults facilitate magma transport through the crust. Our results indicate the existence of two NNE‐oriented seismogenic dextral to dextral‐reverse regional faults that generate a duplex in a continental‐scale fault setting. Inside the duplex, we observed normal to strike‐slip normal focal mechanisms which recurrently have NE trending nodal planes. At a regional scale, a strike‐slip tectonic environment has a N60°E/18° shortening direction and a N151°E/03° extension direction. We conclude that stratovolcanoes are located inside the duplex in a local transtensional environment where NE oriented normal faulting may occur. These faults facilitate magma transport since they represent the preferential orientation for dilatational fractures. Conversely, in local transpressional environments such as the Puyuhuapi fault (NNE oriented dextral to dextral‐reverse kinematics), only minor eruptive centers of small volume are emplaced, suggesting a less productive magma transportation process. Key Points: Crustal seismicity reveals a right‐lateral duplex as the continental‐scale fault setting between 44°00′ and 45°30′ in the Southern Volcanic Zone (SVZ) Stratovolcanoes are located in a local transtensional environment inside the duplex Seismicity is consistent with documented brittle and ductile deformation, suggesting a continuous shear zone deeper than the brittle crust